Anomalous broadening of DMABN electronic spectra in solutions - Tomin, Vladimir I.; Hubisz, Krzysztof (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
The results of spectral broadening study of electronic bands of an archetype molecule with intramolecular charge transfer in the excited state, n-dimethylaminobenzonithrile (DMABN), in polar solvents are discussed. The broadening is anomalously large, it amounts to 8000 cm–1, and manifests itself in both luminescence and excitation spectra. The explanation of the results obtained is based on treating a solution as a set of chemically identical solvates with solute in the centre, which have different energies of the pure electronic transitions. The inhomogeneity is likely to arise due to both the intermolecular effect of luminophor environment on its spectra in polar solvents and the existence of various conformers of DMABN.
Optica Applicata, Vol. 36, 2006, nr 4, s. 475-481
Keywords: optyka; DMABN; luminescence; local-excited and charge transfer states; conformers; relaxation